Application of best practice guidelines for OSCEs—An Australian evaluation of their feasibility and value. (May 2015) - Mitchell, Marion L.; Henderson, Amanda; Jeffrey, Carol; Nulty, Duncan; Groves, Michele; Kelly, Michelle; Knight, Sabina; Glover, Pauline
Summary: Background: Objective Structured Clinical Examinations (OSCEs) are widely used in health professional education and should be based on sound pedagogical foundations. Objectives: The aim of this study is to evaluate the feasibility and utility of using Best Practice Guidelines (BPGs) within an OSCE format in a broad range of tertiary education settings with under-graduate and post-graduate nursing and midwifery students. We evaluated how feasible it was to apply the BPGs to modify OSCEs in a course; students' perspective of the OSCE; and finally, if the BPG-revised OSCEs better prepared students for clinical practice when compared with the original OSCEs. Design: A mixed method with surveys, focus groups and semi-structured interviews evaluated the BPGs within an OSCE. Settings: Four maximally different contexts across four sites in Australia were used. Participants: Participants included lecturers and undergraduate nursing students in high and low fidelity simulation settings; under-graduate midwifery students; and post-graduate rural and remote area nursing students. Results: 691 students participated in revised OSCEs. Surveys were completed by 557 students; 91 students gave further feedback through focus groups and 14 lecturers participated in interviews. At all sites the BPGs were successfully used to modify and implement OSCEs. Students valued the realistic nature of the modified OSCEs which contributed to students' confidence and preparation for clinical practice. The lecturers considered the revised OSCEs enhanced student preparedness for their clinical placements. Discussion and Conclusions: The BPGs have a broad applicability to OSCEs in a wide range of educational contexts with improved student outcomes. Students and lecturers identified the revised OSCEs enhanced student preparation for clinical practice. Subsequent examination of the BPGs saw further refinement to a set of eight BPGs that provide a sequential guide to their application in a way that is consistent with best practice curriculum design principles.